Relationship Between Peers, Self-Control, and Parent Control with Youth Smoking Behaviour - Garut, Maria Magdalena Dewi; Nayoan, Christina R.; Geghi, Cathrin W. D. (Universitas Nusa Cendana, 2023)
Adolescence is a transitional period where individuals enter certain phases in human life. During this transition period, adolescents will usually try to find their identity, make their own decisions and try to be accepted as adults in their environment, which makes many adolescents involved in negative behaviour; one of them is smoking. This study aims to determine the relationship between peers, self-control, and parental control with smoking behaviour in students of SMPN 15 Kupang City. This type of research is quantitative research with a Cross-Sectional Study research design. This research was conducted at SMPN 15 Kupang City. The sample of this study amounted to 73 students using a simple random sampling technique. Variables were analyzed using crosstab. The results showed that there is a relationship between peers, self-control, and parental control with smoking behaviour in students of SMPN 15 Kupang City. It is expected to increase anti-smoking socialization activities, implement democratic parenting and optimize peer groups at school.